2020
DOI: 10.1111/ejh.13360
|View full text |Cite
|
Sign up to set email alerts
|

Primary renal lymphoma: A population‐based analysis using the SEER program (1973‐2015)

Abstract: Objective Primary renal lymphoma (PRL) is defined as a non‐Hodgkin lymphoma (NHL) restricted to kidneys without extensive nodal disease. The literature on epidemiology and outcome in PRL is limited to case reports and small case series. Methods We utilized Surveillance, Epidemiology, and End Result database (1984‐2015) to study the demographic, clinical, and pathological characteristics of PRL. We conducted analysis to assess factors associated with overall survival (OS) and cause‐specific survival (CSS). Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…[15,16] More recently, using RNA sequencing of single cells Stewart et al have demonstrated that lymphatic cells are identifiable within the fetal kidney from the first trimester. [17] Presentation is usually unilateral, with bilateral disease usually reported at 10-20% [11] (though a recent population based analysis reported bilateral disease in only 2.7% of 559 cases with a median age of 72 at presentation) [18]. The commonest presenting symptoms include flank pain and an abdominal mass alongside classical "B" symptoms of fevers, fatigue, weight loss and night sweats.…”
Section: Discussionmentioning
confidence: 99%
“…[15,16] More recently, using RNA sequencing of single cells Stewart et al have demonstrated that lymphatic cells are identifiable within the fetal kidney from the first trimester. [17] Presentation is usually unilateral, with bilateral disease usually reported at 10-20% [11] (though a recent population based analysis reported bilateral disease in only 2.7% of 559 cases with a median age of 72 at presentation) [18]. The commonest presenting symptoms include flank pain and an abdominal mass alongside classical "B" symptoms of fevers, fatigue, weight loss and night sweats.…”
Section: Discussionmentioning
confidence: 99%
“…PRL accounts for approximately 0.7–1% of all non-Hodgkin’s lymphomas (NHL), and diffuse large B cell lymphoma (DLBCL) represents the most prevalent pathological histotype [ 1 ]. The median age at diagnosis ranges from 60 to 70 years, with the prevalence in men [ 2 , 3 ]. Conversely, secondary renal involvement is more frequent and could occur in 30–60% of all NHL [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Typical symptoms of PRL include flank pain, hematuria, weight loss, fever and potential signs of acute or chronic renal failure [ 4 , 5 , 6 ]. PRL has a more frequent monolateral involvement, although bilateral kidney localization could be observed in up to 7.9–20% of cases [ 3 , 7 ]. The disease is typically associated with rapid progression and dismal prognosis, showing a median survival rate of nearly 1 year [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations